A New Detection Method of IGBTs Open-Circuit Faults in an Induction Motor Drive - Hicham Zaimen , Ali Rezig , Said Touati (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Due to the growing demand for the reliability and safety of industrial systems such as induction motor drives (IMDs), it is mandatory to detect all types of potential faults as early as possible to implement a fault -tolerant operation that minimizes the degradation of the performances and avoids dangerous situations. This paper presents a new fault detection and identification (FDI) method applied to an induction motor drive in the case of open IGBTs faults of a three-phase voltage source inverter (VSI). The diagnosis method of the open switch faults proposed in this work is based on the average absolute values of the normalized phase currents. This diagnosis method has some advantages in terms of fast fault detection time, robustness against transients, and it does not require extra hardware and sensors. The effectiveness of the proposed FDI method is verified through computer simulation using MATLAB-SIMULINK software